Fa’aliyatu Istikhdậmi Tharîqah al-Istijậbah al-Jasadiyah al-Kậmilah bi Wasîlati Bithậqah al-Falash Litarqiyati Itsqậni al-Mufradật lada at-Talậmizi fi Madrasati Nûrul Imận al-Mutawassitah al-Islamiyah Indragiri Hilir/ فعالية استخدام طريقة الاستجابة الجسدية الكاملة بوسيلة بطاقة الفلاش لترقية إتقان المفردات لدى التلاميذ في مدرسة نور الإيمان المتوسطة الإسلامية اندراجيري هيلير - anggun sari, yola; ahmad, amrizal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
It was experimental research with pretest and posttest, and it aimed at finding out the effectiveness of using Total Physical Response method with Flash Card media in increasing student vocabulary mastery at Islamic Junior High School of Nurul Iman Indragiri Hilir. The formulation of the problem in this research was